Interactive Video Development With a Scientific-Based Ethnopedagogical Approach for Elementary School Students : An Analysis Review - Raharjo, Makmun; Safitri, Erna Retna; Harlin, Harlin (Pedagogia : Jurnal Pendidikan, 2024)
The aims of this research is to analyze the need for the development of interactive videos with a scientifically based ethnopedagogical approach for elementary school students. This research is a qualitative descriptive study. Data collection was carried out using a questionnaire method with 34 teachers as respondents. The research results show that students' difficulties in learning are mainly caused by teacher explanations that students cannot understand (37 percent). Teachers rarely use ICT-based media (41.2 percent) and most learning uses presentations (38.2 percent) and discussions (38.2 percent). As many as 73.5 percent of teachers use media downloaded from the internet. Barriers to media development are caused by only 14.7 percent of teachers being able to develop their media. Teachers experience difficulties in conveying material to students, so 79.4 percent of teachers want to develop interactive learning media. As many as 97.1 percent of teachers also want media to be developed with a scientific approach, 76.5 percent see the need to introduce local culture to support character education. The results of the analysis of supporting facilities show that 35.3 percent of schools have adequate internet access, 88.9 percent of students have laptops, and 11.1 percent have cell phones. The results of this research indicate the need to develop digital-based learning media to help students in learning. The research results also show that a scientifically based ethnopedagogical approach will be a good synergy in the learning media being developed.